Mastication characterization of horses fed bermudagrass hay in a two-part field study - J. Farmer Long; R. Hutton; A. Abrams; J.A. Duberstein; K.J. Duberstein (Journal of Equine Veterinary Science, 2026)

Genetic and Morphological Evidence for the Transfer of the Lord Howe Island Endemic Fern Lastreopsis nephrodioides to Parapolystichum (Dryopteridaceae) - Leon R. Perrie; Daniel J. Ohlsen; Ian Hutton; Lara D. Shepherd (New Zealand Journal of Botany, 2026)
The lastreopsid ferns currently comprise four genera, with two of them, Lastreopsis and Parapolystichum , poorly delimited morphologically. Attribution of species to Lastreopsis or Parapolystichum has principally been by phylogenetic analysis of chloroplast DNA sequences. The last of the Australasian species of Lastreopsis to have its phylogenetic placement investigated is Lastreopsis nephrodioides , endemic to Lord Howe Island. Phylogenetic analyses of the chloroplast loci rbc L, trn L‐ trn F, rps 4‐ trn S, and trn G‐ trn R place this species in Parapolystichum and accordingly a new combination is made. A detailed description of Parapolystichum nephrodioides is also given and, with a more detailed understanding of morphological differences between the genera, the morphology of the Lord Howe Island species provides additional support for its placement in Parapolystichum : its spores have auriculate projections rather than being echinulate like Lastreopsis subgenus Rhopalotricha ; and its fronds generally have anadromous venation, which is unknown in Australasian species of Lastreopsis subgenus Lastreopsis but found in several other Parapolystichum species.

Tmesipteris eucampta (Psilotaceae), a newly described species for plants of Tmesipteris from Lord Howe Island - Leon R. Perrie; Daniel J. Ohlsen; Alison Kellow; Ian Hutton; Patrick J. Brownsey; Lara D. Shepherd (New Zealand Journal of Botany, 2025)

On the possible activation of quasi-Hilda comets by Jovian tides - J.A. Correa-Otto; E. García-Migani; R. Gil-Hutton (Icarus, 2025)

Activity in quasi-Hilda objects: A photometric approach - E. García-Migani; R. Gil-Hutton; J. Correa-Otto (Icarus, 2025)

Evaluation of physical and chemical modifications to drug reservoirs for stimuli-responsive microneedles - Luchi Li; Qonita Kurnia Anjani; Aaron R. J. Hutton; Mingshan Li; Akmal Hidayat Bin Sabri; Lalitkumar Vora; Yara A. Naser; Yushi Tao; Helen O. McCarthy; Ryan F. Donnelly (Drug Delivery and Translational Research, 2025)
Hydrogel-forming microneedle (MN) arrays are minimally-invasive devices that can penetrate the stratum corneum , the main barrier to topical drug application, without causing pain. However, drug delivery using hydrogel-forming MN arrays tends to be relatively slow compared to rapid drug delivery using conventional needles and syringes. Therefore, in this work, for the first time, different physical and chemical delivery enhancement methods were employed in combination with PVA-based hydrogel-forming MN arrays. Using a model drug, ibuprofen (IBU) sodium, the designed systems were assessed in terms of the extent of transdermal delivery. Iontophoresis (ITP) and heat-assisted drug delivery technology were investigated as physical permeation enhancement techniques. Ex vivo studies demonstrated that the ITP (0.5 mA/cm 2 )-mediated combination strategy significantly enhanced the transdermal permeation of IBU sodium over the first 6 h (~ 5.11 mg) when compared to MN alone (~ 1.63 mg) ( p < 0.05). In contrast, heat-assisted technology showed almost no promoting effect on transdermal delivery. Furthermore, IBU sodium-containing rapidly dissolving lyophilised and effervescent reservoirs, classified as chemical modification methods, were prepared. Both strategies achieved rapid and effective ex vivo IBU sodium permeation, equating to ~ 78% (30.66 mg) and ~ 71% (28.43 mg) from lyophilised and effervescent reservoirs, respectively. Moreover, in vivo pharmacokinetic studies showed that the IBU sodium plasma concentration within lyophilised and effervescent groups reached a maximum concentration (C max ) at 4 h (~ 282.15 µg/mL) and 6 h (~ 140.81 µg/mL), respectively. These strategies not only provided rapid achievement of therapeutic levels (10–15 µg/ml), but also resulted in sustained release of IBU sodium for at least 48 h, which could effectively reduce the frequency of administration, thereby improving patient compliance and reducing side effects of IBU sodium. Graphical Abstract

Dairy on MyPlate: Consumption of Dairy-based Foods Among College Students in the University Dining Space - R. Hutton; K. Ingerson; G. Cox (Journal of the Academy of Nutrition and Dietetics, 2024)

Impact-triggered activation of (2060) Chiron during its 1972 and 2021 outbursts - R. Gil-Hutton (Icarus, 2024)

Exploring the pathology of liver, kidney, muscle, and stomach of fledgling seabirds associated with plastic ingestion - Peter S. Puskic; Ron Slocombe; Richard Ploeg; Lauren Roman; Mary-Anne Lea; Ian Hutton; Andrew R. Bridle (Journal of Hazardous Materials, 2024)

Development and Evaluation of Dissolving Microarray Patches for Co-administered and Repeated Intradermal Delivery of Long-acting Rilpivirine and Cabotegravir Nanosuspensions for Paediatric HIV Antiretroviral Therapy - Kurtis Moffatt; Ismaiel A. Tekko; Lalitkumar Vora; Fabiana Volpe-Zanutto; Aaron R. J. Hutton; Jessica Mistilis; Courtney Jarrahian; Nima Akhavein; Andrew D. Weber; Helen O. McCarthy; Ryan F. Donnelly (Pharmaceutical Research, 2023)
Purpose Whilst significant progress has been made to defeat HIV infection, the efficacy of antiretroviral (ARV) therapy in the paediatric population is often hindered by poor adherence. Currently, two long-acting (LA) intramuscular injectable nanosuspensions of rilpivirine (RPV) and cabotegravir (CAB) are in clinical development for paediatric populations. However, administration requires access to healthcare resources, is painful, and can result in needle-stick injuries to the end user. To overcome these barriers, this proof-of-concept study was developed to evaluate the intradermal delivery of RPV LA and CAB LA via self-disabling dissolving microarray patches (MAPs). Methods Dissolving MAPs of two conformations, a conventional pyramidal and a bilayer design, were formulated, with various nanosuspensions of RPV and CAB incorporated within the respective MAP matrix. MAPs were mechanically robust and were capable of penetrating ex vivo skin with intradermal ARV deposition. Results In a single-dose in vivo study in rats, all ARV MAPs demonstrated sustained release profiles, with therapeutically relevant plasma concentrations of RPV and CAB detected to at least 63 and 28 d, respectively. In a multi-dose in vivo study, repeated MAP applications at 14-d intervals maintained therapeutically relevant plasma concentrations throughout the duration of the study. Conclusions These results illustrate the potential of the platform to repeatedly maintain plasma concentrations for RPV and CAB. As such, these MAPs could represent a viable option to improve adherence in the paediatric population, one that is capable of being painlessly administered in the comfort of the patient’s own home on a biweekly or less frequent basis. Graphical abstract

125 Quantification of chewing frequency in horses consuming bermudagrass hay compared with other popular equine forages - J. Farmer; T. Callaway; J. Duberstein; K. Duberstein; R. Hutton (Journal of Equine Veterinary Science, 2023)

Prediction of enteric methane emissions by sheep using an intercontinental database - Alejandro Belanche; Alexander N. Hristov; Henk J. van Lingen; Stuart E. Denman; Ermias Kebreab; Angela Schwarm; Michael Kreuzer; Mutian Niu; Maguy Eugène; Vincent Niderkorn; Cécile Martin; Harry Archimède; et al. (Journal of Cleaner Production, 2023)

Designing a unique feedback mechanism for hydrogel-forming microneedle array patches: a concept study - Aaron R. J. Hutton; Melissa Kirkby; Eneko Larrañeta; Ryan F. Donnelly (Drug Delivery and Translational Research, 2022)
Although microneedle array patch (MAP) technology is reaching ever closer to regulatory approval, it remains imperative that approaches to further improve patient acceptance are still explored. Addressing this perception, a water-filled reservoir was incorporated into a hydrogel-forming MAP system to provide a novel feedback mechanism. To confirm successful MAP skin insertion, the end user would both hear and feel the rupture of the water-filled reservoir. Interestingly, a 50-µL water-filled reservoir ruptured at 30.27 ± 0.39 N, which has previously been shown as the mean application force for MN insertion in human subjects following appropriate instruction. Importantly, no significant difference in % cumulative permeation of FITC-dextran 10 kDa and fluorescein sodium after 24 h was observed between a 50-µL reservoir and the current method of application that has been successfully used in both in vitro and in vivo studies ( p > 0.05). Therefore, as drug delivery was not affected, this proof-of-concept study has shown that a water-filled reservoir feedback mechanism has the potential to serve as a viable tool for consistent MAP skin insertion. Graphical abstract

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Collective influence of household and community capitals on agricultural employment as a measure of rural poverty in the Mahanadi Delta, India - Tristan Berchoux; Gary R. Watmough; Fiifi Amoako Johnson; Craig W. Hutton; Peter M. Atkinson (Ambio, 2020)

Wrestling with the complexity of evaluation for organizations at the boundary of science, policy, and practice - R. Pitt; C. Wyborn; G. Page; J. Hutton; M. Virah Sawmy; M. Ryan; L. Gallagher (Conservation Biology, 2018)
Boundary organizations are situated between science, policy, and practice and have a goal of supporting communication and collaboration among these sectors. They have been promoted as a way to improve the effectiveness of conservation efforts by building stronger relationships between scientists, policy makers, industry, and practitioners (Cook et al. 2013). Although their promise has been discussed in theory, the work of and expectations for boundary organizations are less defined in practice. Biodiversity conservation is characterized by complexity, uncertainty, dissent, and tight budgets, so boundary organizations face the challenging task of demonstrating their value to diverse stakeholders. We examined the challenges boundary organizations face when seeking to evaluate their work and thus aimed to encourage more productive conversations about evaluation of boundary organizations and their projects. Although no off‐the‐shelf solution is available for a given boundary organization, we identified 4 principles that will support effective evaluation for boundary organizations: engage diverse stakeholders, support learning and reflection, assess contribution to change, and align evaluation with assumption and values.

NiftyPET: a High-throughput Software Platform for High Quantitative Accuracy and Precision PET Imaging and Analysis - Pawel J. Markiewicz; Matthias J. Ehrhardt; Kjell Erlandsson; Philip J. Noonan; Anna Barnes; Jonathan M. Schott; David Atkinson; Simon R. Arridge; Brian F. Hutton; Sebastien Ourselin (Neuroinformatics, 2018)

Detection of infectious bronchitis virus 793B, avian metapneumovirus, Mycoplasma gallisepticum and Mycoplasma synoviae in poultry in Ethiopia - S. Hutton; J. Bettridge; R. Christley; T. Habte; K. Ganapathy (Tropical Animal Health and Production, 2017)

Geological Advances in the Sydney Basin: introduction to the thematic issue - C. R. Ward; A. C. Hutton; H. N. Bowman; K. L. Pinetown (Australian Journal of Earth Sciences, 2014)

The quandary of quota management in the T orres S trait rock lobster fishery - I. van Putten; R. Deng; D. Dennis; T. Hutton; S. Pascoe; E. Plagányi; T. Skewes (Fisheries Management and Ecology, 2013)
Islanders, commercial non‐indigenous fishers and P apua N ew G uinea fishers share the tropical rock lobster fishery, P anulirus ornatus ( F abricius) in T orres S trait. As the fishery is in the process of moving from input to output controls, a pre‐implementation understanding of indigenous fishers' perceptions of the potential impact of different quota management systems is gained. This study, based on workshops and interviews, considers the impact of competitive quota, community quota and a hybrid system with individually tradeable quota ( ITQ ), and broadens the current biological focus of fisheries management through consideration of economic, social and cultural aspects. The perceived quota system impact on indigenous lobster fishers largely mirrors the experience internationally, with unlimited access and self‐determination considered most important. The heterogeneity of the indigenous sector increases the management complexity for this fishery, but needs to be taken into consideration if unexpected consequences of the chosen quota management system are to be avoided.

Outbreak of angular leaf spot, caused by Xanthomonas fragariae, in a Queensland strawberry germplasm collection - Anthony J. Young; Thomas S. Marney; Mark Herrington; Don Hutton; Apollo O. Gomez; Adam Villiers; Paul R. Campbell; Andrew D. W. Geering (Australasian Plant Pathology, 2011)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Field resistance of annual pasture legumes to the root lesion nematode, Pratylenchus neglectus - R. A. Ballard; R. E. Hutton; S. P. Taylor; A. C. McKay; J. H. Howie (Australasian Plant Pathology, 2006)

Laboratory Kinetic Studies of the Reactions of Cl Atoms with Species of Biogenic Origin: δ3-Carene, Isoprene, Methacrolein and Methyl Vinyl Ketone - Carlos E. Canosa-Mas; Hilary R. Hutton-Squire; Martin D. King; David J. Stewart; Katherine C. Thompson; Richard P. Wayne (Journal of Atmospheric Chemistry, 1999)

Ionic imbalance as a source of toxicity in an estuarine effluent - W. S. Douglas; S. S. Grasso; D. G. Hutton; K. R. Schroeder (Archives of Environmental Contamination and Toxicology, 1996)

Genetics of aryl hydrocarbon hydroxylase induction in mice: Response of the lung to cigarette smoke and 3-methylcholanthrene - R. K. Abramson; B. A. Taylor; D. Tomlin; J. J. Hutton (Biochemical Genetics, 1977)